Payroll Decision Support System for Production Employees Based on Key Performance Indicators Using the Simple Additive Weighting Method - Tegar Bangun Suganda; Intan Dzikria (Department of Information Systems and Technology, Faculty of Intelligent Electrical and Informatics Technology, Universitas 17 Agustus 1945 Surabaya, 2025)
CV. XYZ is a Micro, Small, and Medium Enterprise (MSME) engaged in plastic sack sewing services and implements a piece rate pay system. The company faces obstacles in managing performance-based payroll, which impacts operational efficiency and payment accuracy. This study aims to develop a Payroll Decision Support System (DSS) to record and evaluate the work results of production employees using Key Performance Indicators (KPIs). KPI evaluation is applied as the main criteria in weighting using the Simple Additive Weighting (SAW) method, to produce optimal performance scores. The implementation of KPI-based incentives is expected to improve employee performance while encouraging a productive and transparent work culture. Blackbox testing shows that 97% of the test data meets user requirements, indicating that the system can run according to specifications. The results of this study contribute to the integration of KPIs and SAW in assessing production employee performance for fair and effective payroll decision-making, as well as helping companies implement efficient management practices.